Donor characteristics and their impact on kidney transplantation outcomes: Results from two nationwide instrumental variable analyses based on outcomes of donor kidney pairs accepted for transplantation. (August 2022) - Schaapherder, Alexander F.; Kaisar, Maria; Mumford, Lisa; Robb, Matthew; Johnson, Rachel; de Kok, Michèle J.C.; Bemelman, Frederike J.; van de Wetering, Jacqueline; van Zuilen, Arjan D.; Christiaans, Maarten H.L.; Baas, Marije C.; Nurmohamed, Azam S.; et al.
Summary: Background: Donor-characteristics and donor characteristics-based decision algorithms are being progressively used in the decision process whether or not to accept an available donor kidney graft for transplantation. While this may improve outcomes, the performance characteristics of the algorithms remains moderate. To estimate the impact of donor factors of grafts accepted for transplantation on transplant outcomes, and to test whether implementation of donor-characteristics-based algorithms in clinical decision-making is justified, we applied an instrumental variable analysis to outcomes for kidney donor pairs transplanted in different individuals. Methods: This analysis used (dis)congruent outcomes of kidney donor pairs as an instrument and was based on national transplantation registry data for all donor kidney pairs transplanted in separate individuals in the Netherlands (1990-2018, 2, 845 donor pairs), and the United Kingdom (UK, 2000-2018, 11, 450 pairs). Incident early graft loss (EGL) was used as the primary discriminatory factor. It was reasoned that a scenario with a dominant impact of donor variables on transplantation outcomes would result in high concordance of EGL in both recipients, whilst dominance of asymmetrical outcomes could indicate a more complex scenario, involving an interaction of donor, procedural and recipient factors. Findings: Incidences of congruent EGL (Netherlands: 1·2%, UK: 0·7%) were slightly lower than the arithmetical (stochastic) incidences, suggesting that once a graft has been accepted for transplantation, donor factors minimally contribute to incident EGL. A long-term impact of donor factors was explored by comparing outcomes for functional grafts from donor pairs with asymmetrical vs. symmetrical outcomes. Recipient survival was similar for both groups, but a slightly compromised graft survival was observed for grafts with asymmetrical outcomes in the UK cohort: (10-years Hazard Ratio for graft loss: 1·18 [1·03-1·35] p<0·018); and 5 years eGFR (48·6 [48·3–49·0] vs. 46·0 [44·5–47·6] ml/min in the symmetrical outcome group, p<0·001). Interpretation: Our results suggest that donor factors for kidney grafts deemed acceptable for transplantation impact minimally on transplantation outcomes. A strong reliance on donor factors and/or donor-characteristics-based decision algorithms could result in unjustified rejection of grafts. Future efforts to optimize transplant outcomes should focus on a better understanding of the recipient factors underlying transplant outcomes. Funding: None.